Acute myeloid leukemia in patients older than 75: prognostic impact of FLT3-ITD and NPM1 mutations. Issue 1 (January 2015) - Hirsch, Pierre; Qassa, Ghazi; Marzac, Christophe; Tang, Ruoping; Perrot, Jean-Yves; Isnard, Françoise; Mohty, Mohamad; Marie, Jean Pierre; Legrand, Ollivier
Abstract The benefit associated with chemotherapy in older patients with acute myeloid leukemia (AML) is debated. The prognostic impact of molecular mutations in these patients is unknown. We identified 79 patients with AML aged 75 years or over. Forty-two received chemotherapy and 37 supportive care only. In intensively treated patients, overall survival was longer (p < 0.001). Achieving complete remission was associated with longer survival (p < 0.001). NPM1 mutations tended to be associated with a higher complete remission rate (p = 0.12). In multivariate analysis, FLT3-ITD was associated with poorer survival (p = 0.049). Patients harboring FLT3-ITD and no NPM1 mutation had a poorer prognosis than others (p = 0.02). Intensive treatments can benefit a portion of elderly patients. FLT3-ITD and NPM1 mutational status might be useful for prognosis stratification.